(untitled) (American Journal of Business Management, Economics and Banking, 2026)
This at work economy driver subjects financing mechanism improvement theoretical and practical aspects and this in process international of experience place studied. Research during enterprises financing sources diversification, state and private sector partnership, bank loans, venture capital, crowdfunding and state guarantee funds such as financial of instruments efficiency analysis It has also been developed and developing in the countries used financing models between differences and their national to the economy adaptation opportunities seeing Research as a result economy driver of subjects financial stability increase, investment activity reinforcement and economic efficiency to provide aimed at scientific and practical offers working This is a approaches of enterprises competitiveness increase and in the economy stable to grow to provide service does.